TINDAK PIDANA KESOPANAN DIBIDANG KESUSILAAN ( PERZINAHAN ) DALAM KUHP SERTA PADANANNYA DENGAN HUKUM PIDANA ADAT - Danu Krisnawan, Ida Bagus Made (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 4 No 2 (2015)DO - 10.24843/JMHU.2015.v04.i02.p08, 2015)
Adultery that in terms of customary criminal law known as drati karma a deviant act and violates decency offense under customary law. It is considered a serious offense and is a destructive act of moral and behavior that damages the harmony and balance, causing impure state (cuntaka). From the description that has been proposed, as for the formulation of the problem that arises in this paper is: "Does Crime Decency act in the field of ethics (Adultery) who had been sentenced to criminal sanctions in accordance with the Criminal Code may also be subject to criminal sanctions custom?" This type of research used in this research is the research journal of law by using the approach of normative aspect in this case means that the laws of science research using normative legal research. Normative legal research done through the inventory of positive law as a basic introduction before conducting research activities. The study results showed that the process of law enforcement by law enforcement officers in the enforcement of national legislation (the Criminal Code) and village that enforce local village who was born based on local wisdom each more attention and importance of concepts of justice. Legal certainty is applied based on the Law and the Constitution of the Pancasila. Law enforcement does not mean sanctions but tends to give priority to justice (Restorative Justice) so that the public at large can understand, be aware of and comply with applicable norms.
Keywords: Adultery, Decency, Indigenous Criminal, Criminal General (Criminal Code)